MODEL-PLANT MISMATCH DETECTION, ISOLATION AND ESTIMATION USING MISMATCH MODELING - KAMAL IQBAL, NUR HIDAYAH (2015)
The performance of MPC highly depends on the accuracy of the model of the plant used in the design of MPC. The difference between the model of the plant and the actual dynamic and steady state characteristics of the plant is called model plant mismatch (MPM). Even though MPC can tolerate some amount of mismatch, excessive MPM can significantly deteriorate the performance of the controller. In MIMO systems re-identification of complete plant is very costly and time consuming. This research aims at developing a method for detecting submodels that have significant mismatch, estimating the magnitude of the mismatch and isolating those submodels that have significant mismatches to deteriorate the performance of the controller.